2021
DOI: 10.1002/pssa.202100655
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pull Speed and Heat Treatment on Thermal Donors in Czhocralski Silicon

Abstract: In silicon crystals manufactured by the Czochralski method, oxygen is incorporated as a contaminant originating primarily from dissolution of the quartz crucible used to contain the molten silicon feedstock. The oxygen can be found either as interstitials, agglomerates, or as oxide particles. Particular kinds of agglomerates are known to lead to the formation of thermal donors—electronic states in the bandgap of the silicon base material. These can act as sites for recombination of excited charge carriers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…[2,3,23] TDs are known to be aggregates of a few O i atoms, whose density (number per volume) increases with duration within the generation temperature range, similar to OP nuclei. [16,17] Recently, Olsen et al found an inverse correlation of TD density with pulling rate during Cz manufacturing, [24] which can be attributed to a change in duration within the generation temperature range. Furthermore, TDs act as double donors and therefore influence the resistivity of the wafers below 500 °C.…”
mentioning
confidence: 99%
“…[2,3,23] TDs are known to be aggregates of a few O i atoms, whose density (number per volume) increases with duration within the generation temperature range, similar to OP nuclei. [16,17] Recently, Olsen et al found an inverse correlation of TD density with pulling rate during Cz manufacturing, [24] which can be attributed to a change in duration within the generation temperature range. Furthermore, TDs act as double donors and therefore influence the resistivity of the wafers below 500 °C.…”
mentioning
confidence: 99%